Logistic capabilities and competitive advantage: a case of logistic SMES in Penang / Mohd Firdaus Ruslan ... [et al.] - Ruslan, Mohd Firdaus; Ismail, Mahazir; Mohamad Kamarudin, Arshad (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
With the rapid progress of information technology, innovation and globalization, logistic firms have been in a new era of competition between supply chains. Logistics and supply chain management have become one of the sources of sustainable competitive advantage and also the most essential element for supply chain success. To gain competitive advantage, logistic firms must not only focus on logistics assets but also focus on creating logistics capabilities. Thus, the aim of this study is to examine the relationship of logistics capabilities and competitive advantage. Two logistics capabilities that have been used in this study which are information focus and customer focus. By using a systematic sampling technique, a sample of 40 logistics firm in Penang was used for the investigation. From the result of multiple regression, it showed that only logistics information focus has relationship with competitive advantage. On the other hand, logistics customer focus failed to show effect on competitive advantage in this study. The findings of this research can help future researcher to understand on the two logistics capabilities since very limited research are found in this area particularly in the Malaysia context. Moreover, the findings would help SMEs in Malaysia to understand how competitive advantage can be gained by focusing on logistics capabilities.